2015
DOI: 10.1371/journal.pone.0118301
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hs-CRP, D-Dimer and Fibrinogen in Differentiating Etiological Subtypes of Ischemic Stroke

Abstract: The aim of this study was to evaluate the diagnostic value of the serum biochemical markers high-sensitivity C-reactive protein (hs-CRP), D-dimer (DD) and fibrinogen (Fg) in differentiating etiological subtypes of ischemic stroke. This study was a retrospective case-only study, consecutively including patients with acute ischemic stroke. All patients were classified into subtypes using the TOAST classification system. A total of 317 patients were evaluated. Hs-CRP and DD levels were significantly different amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 28 publications
2
37
0
2
Order By: Relevance
“…There was a significant difference between cardioembolic and atherosclerotic groups and between cardioembolic and lacunar groups and between cardioembolic and undermined/other groups. This coincides with Liu [20] who found that D-dimer levels were significantly different among the subtypes and were the highest in cardioembolic followed by large artery atherosclerosis and small artery occlusion. In contrast to our results, Takano et al [21] found marked elevation of plasma concentration of D-dimer was observed only in cardioembolic versus control within 48 h of onset persisting for 1 month with a gradual decline.…”
Section: Discussionsupporting
confidence: 89%
“…There was a significant difference between cardioembolic and atherosclerotic groups and between cardioembolic and lacunar groups and between cardioembolic and undermined/other groups. This coincides with Liu [20] who found that D-dimer levels were significantly different among the subtypes and were the highest in cardioembolic followed by large artery atherosclerosis and small artery occlusion. In contrast to our results, Takano et al [21] found marked elevation of plasma concentration of D-dimer was observed only in cardioembolic versus control within 48 h of onset persisting for 1 month with a gradual decline.…”
Section: Discussionsupporting
confidence: 89%
“…The combination of hs‐CRP and D‐dimer improves the diagnosis accuracy of cardioembolism in the acute phase . Higher hs‐CRP level and lipoprotein‐related phospholipase A2 (Lp‐PLA2) activity are significantly associated with more severe neurologic impairment and larger infarct size in patients who have AIS . Hs‐CRP and homocysteine are independent predictors of short‐term outcome and mortality after AIS.…”
Section: Discussionmentioning
confidence: 66%
“…Especially D-dimer was effective in identifying IS etiology [181,182] and showed good prognostic accuracy as predictor of short- and long-term worse outcome [182,183,185,186]. Similar results were also reported for E-selectin and VCAM-1, but those data required further validation in additional large-cohort studies [184].…”
Section: Inflammatory Mediators As Potential Diagnostic or Prognosmentioning
confidence: 78%
“…Furthermore, specific challenges regarding biomarkers of central nervous tissue include the penetration of BBB and the lack of correlation between functional symptoms and volume (as opposed to location) of injured tissue. According to pathophysiological processes underlying IS, potential inflammatory biomarkers may be classified as released by: (i) astroglial activation and neuronal injury (Table 1) [146,147,148,149,150,151,152,153,154,155,156,157]; (ii) systemic inflammatory response (Table 2) [158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177,178,179]; (iii) dysfunctional endothelium (Table 3) [180,181,182,183,184,185,186] (Figure 4). …”
Section: Inflammatory Mediators As Potential Diagnostic or Prognosmentioning
confidence: 99%